2005
DOI: 10.1038/sj.bjc.6602885
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of care and survival for patients aged under 40 years with bone sarcoma in Britain, 1980–1994

Abstract: The purpose of the study was to calculate population-based survival rates for osteosarcoma (OS) and Ewing's sarcoma (ES) in Great Britain during 1980 -1994, determine proportions of patients treated at specialist centres or entered in national and international clinical trials, and investigate effects of these factors on survival. Data on a population-based series of 1349 patients with OS and 849 with ES were compiled from regional and national cancer registries, UK Children's Cancer Study Group, regional bone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
35
0
5

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(45 citation statements)
references
References 32 publications
5
35
0
5
Order By: Relevance
“…For osteosarcoma and Ewing sarcoma, 5-year survival also improved from 37 to 61% and from 34 to 66%, respectively over this period (Stiller et al, 2006a). We describe the incidence and survival from bone tumours at ages 0 -14 years in northern England and the West Midlands during the period 1981-2002, updating previous analyses (Cotterill et al, 2000Stiller et al, 2006c).…”
supporting
confidence: 63%
See 1 more Smart Citation
“…For osteosarcoma and Ewing sarcoma, 5-year survival also improved from 37 to 61% and from 34 to 66%, respectively over this period (Stiller et al, 2006a). We describe the incidence and survival from bone tumours at ages 0 -14 years in northern England and the West Midlands during the period 1981-2002, updating previous analyses (Cotterill et al, 2000Stiller et al, 2006c).…”
supporting
confidence: 63%
“…Gender was not significant in relation to survival for osteosarcoma or Ewing sarcoma, as reported for Ewing sarcoma in the United Kingdom (Stiller et al, 2006c). However, a recent study of Ewing sarcoma from the United States of America has reported a higher 5-year survival rate in females than males (Esiashvili et al, 2008).…”
Section: Discussionmentioning
confidence: 65%
“…However, reports from the area of head and neck cancer are rare [28][29][30]. In the present study, surgery was performed in university centres or regional hospitals and there was some indication that survival was higher in patients from university centres than from other hospitals.…”
Section: Discussionmentioning
confidence: 89%
“…To our knowledge, only three nationwide, population-based studies on clinical presentation and prognosis of osteosarcoma have been publishedbut without histological reexamination (Larsson and Lorentzon 1974, Curry et al 2006, Stiller et al 2006. Stiller et al (2006) collected information on all patients with osteosarcoma in Britain during 1980-1994 from the National Registry of Childhood Tumours, regional cancer registries in England, the national cancer registries in Scotland and Wales, the UK Children's Cancer Study Group register, special bone tumor centers, and the Birmingham Bone Tumour Service.…”
Section: Discussionmentioning
confidence: 99%